Emotional regimes in the political economy of the "welfare service state": The case of continuing education and active inclusion in Germany - Sigrid Betzelt; Ingo Bode (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
One of the most prominent trends in Western welfare capitalism during the last decades has been the expansion of welfare services as an outcome of the transition from the Fordist to a 'post-industrial' settlement, driven by changes in the wider society and the economic system. The advent of what has been called a 'welfare service state' is part and parcel of a broader transformation propelled by the paradigms of 'activation' and 'social investment', with all the ambiguities endemic to intentions to ensure a more egalitarian distribution of human capital by an increased commodification of labour. These ambiguities impact upon the universe of welfare service provision which must deal with incompatible rationales, that is, a market and business logic on the one hand, and 'professional' and ethical norms on the other. Inspired by the 'cultural political economy' approach, we contend that insights into the 'mental processing' of human services by specialised organisations under these institutional conditions are crucial for understanding the chemistry of contemporary welfare capitalism more generally. To capture the role of the welfare service sector in the current settlement, we draw on findings from the field of continuing and vocational education for jobseekers and young people - a sector which has been largely neglected by the public debate in recent years, despite its growing importance in times of ongoing technological change. Our paper is based on qualitative case studies conducted in two regions of Germany, and our research concept borrows from different bodies of theory that deal with the political economy and sociology of the welfare state, human service organisations, and with emotional work. First, we explore the organisational dynamics of welfare service providers in their interaction with a quasi-market- based governance model; secondly, we scrutinize the sense-making of the service-providing personnel with an eye on how it is influenced by the conflicting rationales mentioned above. More specifically, we argue that emotional dynamics within the organisational settings under scrutiny are an important catalyst in the transformation of the political economy of contemporary welfare capitalism, moderating the interplay of institutional governance, organisational steering, and individual self-management. The mechanisms at play are conceptualised as emotional regimes which make the welfare service sector work despite its institutionalised precarity - even during the Covid-19 pandemic that can be seen as an 'eye-opener' to longstanding problems of the sector under study. Our analysis also suggests that there may be a tipping point at which these mechanisms cease to accommodate the post-industrial settlement of a 'recommodified' welfare capitalism.
Keywords: I21; I38; J08; J81; L84; P16; 330; welfare state; labour market; human services; continuing education; governmentality; NPM